THE ROLE EXERCISED BY PRONAF IN SMALL MUNICIPALITIES IN THE WEST OS SAO PAULO - Souza, Paulo Cesar [UNESP]; Hespanhol, Antonio Nivaldo [UNESP] (Univ Estado Rio Janeiro, 2016)
From the early 1990, with the resumption of the democratic process and the new national Constitution ( 1988), some public policies were being implemented by the Federal Government with ways to benefit the farmers, especially the class of small and medium producers, today known as family agriculture. The most important and effective of these was the PRONAF, that serve low-income rural producers, rural residentsand and/or in the municipalities where they have property and that depend on almost exclusively of the agricultural production for family sustenance. The PRONAF has swept through the national territory and its resources could be obtained by producers of all Brazil. This text examines the role exercised by program in small municipalities situated in the West of Sao Paulo, and tries to understand the influence of this public policy in local economies, checking if the positive aspects regarding the shared participation of the Government, the associations of producers and Landowners on the uptake and use of incentives, with ways to boost of territorial development.
Keywords: Family agriculture; Pronaf; West of Sao Paulo; Territorial Development